Evaluasi Kinerja Ruas Jalan Jenderal Sudirman Kota Gorontalo Akibat Parking on The Street - Dhea Nur Amanah Hadjarati; Frice Lahmudin Desei; Yuliyanti Kadir (Transbahasa, 2025)
Jenderal Sudirman road is one of the main road in Gorontalo City with a high traffic volume. This condition is worsened by the presence of on-street parking, which disrupts traffic flow and reduces road performance. This study aims to evaluate the impact of on-street parking on the performance of Jenderal Sudirman Road using the 1997 Indonesian Highway Capacity Manual (MKJI 1997) as a reference. Data collection was conducted over three days: Tuesday, June 11, 2024, Friday, June 14, 2024, and Saturday, June 15, 2024. The analysis of existing conditions shows that the worst road service level occurred on Tuesday, June 11, 2024, with a degree of saturation of 0.58, categorized as service level C, indicating moderate traffic density with limited speed. However, in the absence of on-street parking, the service level improves significantly to a degree of saturation of 0.30, classified as service level B. These findings confirm that on-street parking significantly impacts the efficiency and optimal performance of road sections. Therefore, strict parking management strategies are recommended to improve traffic flow and enhance road service levels in Gorontalo City.